2020
DOI: 10.1002/evl3.177
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variation mediates the evolution of anticipatory parental effects

Abstract: Theory maintains that when future environment is predictable, parents should adjust the phenotype of their offspring to match the anticipated environment. The plausibility of positive anticipatory parental effects is hotly debated and the experimental evidence for the evolution of such effects is currently lacking. We experimentally investigated the evolution of anticipatory maternal effects in a range of environments that differ drastically in how predictable they are. Populations of the nematode Caenorhabdit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 55 publications
(113 reference statements)
1
39
0
Order By: Relevance
“…S1). Interestingly, a recent study has found that C. remanei nematodes cope relatively better in elevated temperatures only if temperatures in previous generations were stably high or were gradually increasing in a “predictable” manner( 60 ). In accordance with the second prediction of the model, h igh i ncidence of m ales (Him phenotype) was documented in worms grown at elevated temperatures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1). Interestingly, a recent study has found that C. remanei nematodes cope relatively better in elevated temperatures only if temperatures in previous generations were stably high or were gradually increasing in a “predictable” manner( 60 ). In accordance with the second prediction of the model, h igh i ncidence of m ales (Him phenotype) was documented in worms grown at elevated temperatures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 12, 2021. ; https://doi.org/10.1101/2021.04.12.439424 doi: bioRxiv preprint 28 28 account for at least some of variation in results observed in empirical studies of TWP. Instead, we have shown that even if we restrict ourselves to experiments with information-only cues, we should expect to observe considerable variation in their results, as a function of variation in parental priors, the reliability of the cues in the different treatments, differences in the duration of cue-exposure for parents and offspring, and the extent to which information from parents was either devalued or degraded in comparison to information from offspring.…”
Section: Discussionmentioning
confidence: 99%
“…as a result of natal dispersal in spatially heterogeneous environments [11,14] or as a result of temporal shifts in environmental conditions that may occur between generations [7,11]. The results of recent studies of experimental evolution in nematodes support the hypothesis that temporal autocorrelation for the environments of parents and offspring encourage the evolution of transgenerational plasticity, by showing that parental experiences had adaptive effects on offspring traits in lineages which evolved when the environmental conditions during the parental and offspring generation were strongly correlated with one another, but not in lineages in which they were not [28,29].…”
Section: Introductionmentioning
confidence: 86%
“…Given such complications, experimental evolution and other explicit tests of fitness (e.g., competition studies) are critical. Experimental evolution in C. elegans and C. remanei suggests that anticipatory maternal effects, which fall under the umbrella of adaptive multigenerational plasticity, can evolve in scenarios where environmental conditions in one generation reliably predict conditions in the next generation ( Dey et al, 2016 ; Lind et al, 2020 ). Furthermore, experimental evolution and modeling of more complex scenarios suggests that anticipatory responses acting over two generations can also evolve ( Proulx et al, 2019 ).…”
Section: Opportunities To Strengthen the Case For Adaptive Multigenermentioning
confidence: 99%